The Impact of Demographical Variables on Organizational Commitment of Employees In Tribhuvan University - Poudel, Surya Prasad (Tribhuvan University Journal, 2024)
Organizational commitment is concerned to maintaining the long term relation with employee for enhancing the organizational performance. It is the major challenging factor to every organization. The previous studies showed age, gender, year of services and educational qualification has significant impact on organizational commitment. This study have aims to assess the organizational commitment level according to the studied demographic variables and their impact on organizational commitment of official employees at TU. The 106 purposive randomly selected official employees’ opinions are analyzed by using 24 items organizational commitment structured questionnaire with 6 point Likert scale. The mean value analysis showed that the commitment level of official employees ranging between slightly committed to moderate commitment level with remarkable standard deviation. The significant number of slightly commitment level of employees with significant standard deviation refers, employees at TU are not fully committed. On the other hand, official employees have age less than 40 years and year of services less than 15 years have found slightly committed. The results showed that, younger employees are searching the alternative opportunity. The ANOVA analysis has shown that demographic variables have impact on organizational commitment. But the difference of impact has found differences according to year of services. The policy maker of TU should solve the prospective official employees’ related problems by amendment of the existing human resource policy.